2016
DOI: 10.1063/1.4962282
|View full text |Cite
|
Sign up to set email alerts
|

High pressure and time resolved studies of optical properties of n-type doped GaN/AlN multi-quantum wells: Experimental and theoretical analysis

Abstract: High-pressure and time-resolved studies of the optical emission from n-type doped GaN/AlN multi-quantum-wells (MQWs) with various well thicknesses are analysed in comparison with ab initio calculations of the electronic (band structure, density of states) and optical (emission energies and their pressure derivatives, oscillator strength) properties. The optical properties of GaN/AlN MQWs are strongly affected by quantum confinement and polarization-induced electric fields. Thus, the photoluminescence (PL) peak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 61 publications
0
17
0
Order By: Relevance
“…However, in optoelectronic devices, such as light-emitting diodes (LEDs) or laser diodes (LDs), the QCSE should be reduced as much as possible. Associated with the spectral shift, there is a separation of electrons and holes within the structure, which reduces the overlap of electron/hole wavefunctions and consequently the radiative recombination rate and the emission efficiency [ 9 , 10 , 11 , 12 , 16 , 17 ]. The majority of nitride-based optoelectronic devices are based on polar multi-quantum wells (MQWs), with heterointerfaces perpendicular to the polarization axis, so that polarization effects are particularly strong.…”
Section: Introductionmentioning
confidence: 99%
“…However, in optoelectronic devices, such as light-emitting diodes (LEDs) or laser diodes (LDs), the QCSE should be reduced as much as possible. Associated with the spectral shift, there is a separation of electrons and holes within the structure, which reduces the overlap of electron/hole wavefunctions and consequently the radiative recombination rate and the emission efficiency [ 9 , 10 , 11 , 12 , 16 , 17 ]. The majority of nitride-based optoelectronic devices are based on polar multi-quantum wells (MQWs), with heterointerfaces perpendicular to the polarization axis, so that polarization effects are particularly strong.…”
Section: Introductionmentioning
confidence: 99%
“…We demonstrated that SL effect of wave functions hybridization is dominant for narrow wells, whereas for wider wells the effect of internal electric field is more important. It is predicted theoretically, that the PL emission intensity should drop with the increasing widths of SL layers, especially with barrier thickness, as was shown for GaN/AlN SLs 19 . The results of the band gap calculations for In 0.33 Ga 0.67 N/GaN SLs were compared with the recent experimental PL data and good agreement was obtained.…”
Section: Resultsmentioning
confidence: 66%
“…Multiple quantum well (MQW) structures and superlattices based on III-nitrides are extensively used in light emitting diodes with high luminescent efficiency (LEDs) and laser diodes for various applications in photonic devices operating in a wide optical range [1][2][3][4][5][6]. Specifically, AlN/GaN MQW structures are used for LEDs emitting in the visible-ultraviolet spectral range [1,7] and solid-state THz optoelectronics [8,9]. Investigation and development of these materials and devices requires advanced materials' characterization techniques examining structural, optical, and electronic properties.…”
Section: Introductionmentioning
confidence: 99%